First results from post-COVID inpatient rehabilitation - Kupferschmitt, Alexa; Langheim, Eike; Tüter, Haris; Etzrodt, Franziska; Loew, Thomas H.; Köllner, Volker (Frontiers in Rehabilitation Sciences, 2023)
Background. COVID-19 is associated with various symptoms and psychological involvement in the long term. In view of the multifactorial triggering and maintenance of the post-COVID syndrome, a multimodal therapy with somatomedical and psychotherapeutic content is expedient. This paper compares the psychological stress of post-COVID patients and their course in rehabilitation to psychosomatic and psychocardiological patients. Method. Observational study with control-groups and clinical, standardized examination: psychological testing (BDI-II, HELATH-49), 6-MWT as somatic parameter, two measurement points (admission, discharge). Sample characteristics, including work related parameters, the general symptom-load and the course of symptoms during rehabilitation are evaluated. Results. At admission in all measures post-COVID patients were significantly affected, but less pronounced than psychosomatic or psychocardiological patients (BDI-II post-COVID = 19.29 ± 9.03, BDI-II psychosomatic = 28.93 ± 12.66, BDI-II psychocardiology = 24.47 ± 10.02). During rehabilitation, in all complaint domains and sub-groups, symptom severity was significantly reduced (effect sizes ranging from d = .34 to d = 1.22). Medium positive effects were seen on self-efficacy (d = .69) and large effects on activity and participation (d = 1.06) in post-COVID patients. In the 6-MWT, the walking distance improved by an average of 76.43 ± 63.58 meters (d = 1.22). Not a single patient deteriorated in walking distance, which would have been a possible sign of post exercise malaise (PEM). Conclusion. Post-COVID patients have a slighter psychological burden as psychocardiological or psychosomatic patients. Although rehabilitation is not curative, post-COVID patients benefit significantly from the interventions and there were no signs of PEM.